Essays on the economic development of Africa - De Vries, Egbert (The Hague : Mouton & Co. N.V. Publishers, 1968)
A compilation of papers presented at the annual lecture programmes of the Bank of Sudan aimed at fulfilling its role in the diffusion of knowledge on economic, monetary and financial affairs and in the interest of the country$1 (Bs economic growth. Topics covered include: development of Africa; Infrastructure and productive investment in Africa; the development of Sudan; and the role of foreign resources in the development of Arica.s
First series of annual lectures on development organized by the Bank of Sudan, Khartoum.
Includes bibliographical references.
lje 25/01/2018
Ref
Keywords: Economic development; Africa